THE EFFECT OF COMPANY SIZE AND LIQUIDITY ON CAPITAL STRUCTURE - Sarah Mutiara; Nana Diana (COMPETITIVE, 2022)
The purpose of this study was to determine whether company size and liquidity have a partial and silmutant effect on the capital structure. The independent variables in this study are company size and liquidity. Meanwhile, the dependent variable in this study is the capital structure. The population in this study were companies registered in the Jakarta Islamic Index (JII) for the period 2017 - 2019. The sample used in this study were 19 companies over a period of 3 years with a total of 57 samples selected using the purposive sampling method. The analysis method used in this research is descriptive statistical analysis, classical assumption test and hypothesis testing using SPSS 25 software. From the results of testing Hypothesis 1 shows that firm size has a positive and significant effect on capital structure. Hypothesis 2 shows that liquidity has a negative and significant effect on capital structure. Meanwhile, Hypothesis 3 shows that firm size and liquidity have a positive and significant effect on the capital structure. This research is expected to add insight and reference in science, governance and other fields.